Religious Solidarity of Youths Through Organisations in Broadcasting the Aqidah of Islam in Starch - Nur Fatinatur Rakhman; Nur Khasanah (ADP Publisher, 2024)
The propagation of Islamic aqeedah is an important responsibility for all Muslims and the youth is one of the groups that have a role in the efforts to spread aqeedah. The religious solidarity of the youth in broadcasting the Islamic aqeedah is an important aspect in maintaining and strengthening the sustainability of religion in the midst of global challenges. Religious solidarity can form a spirit of unity and concern among religious people in defending religious values. so that the role of youth has great strength in spreading the Aqidah Islam through various means. The existence of religious solidarity among youth to support each other in an effort to broadcast the Aqidah Islam consistently and accurately by involving youth from various backgrounds so as to expand understanding and tolerance between religious communities. In spreading the Islamic Aqeedah among youththey must have a deep understanding of Aqeedah so that youth can become agents of positive change in society and can be role models for the younger generation who can uphold the tolerant and peaceful values of Islamic Aqeedah.